First record of giant anteater (Myrmecophaga tridactyla - Myrmecophagidae) in Campos das Vertentes, Minas Gerais - Glauco Cássio de Sousa Oliveira; Taiguara Pereira de Gouvêa; Marcos Magalhães de Souza (Revista Agrogeoambiental, 2023)
The species Myrmecophaga tridactyla, Myrmecophagidae, is widely distributed in the Neotropics regions and is popularly known as the giant anteater. It is considered a generalist species regarding habitat and can be found in human-modified areas such as pastures and crops. However, there is limited information about the species in agricultural ecosystems. Due to its threatened status and the absence of records in the Campos das Vertentes region, which has only 1.04% of its area included in Conservation Units, this study aimed to report the unprecedented occurrence of M. tridactyla in the municipality of Ritápolis, Campos das Vertentes, Minas Gerais, in a transitional region between the Atlantic Forest and the Cerrado. Two occasional records were made on a rural road in this municipality. Therefore, this record increases our knowledge about the spatial distribution of M. tridactyla in the state of Minas Gerais, provides information about the species in human-modified landscapes, and supports the need for more Conservation Units in the Campos das Vertentes region.